Emergency surgery in patients in extremis from blunt torso injury: heroic surgery or futile care?. Issue 4 (18th June 2004) - Brooks, A; Davies, B; Richardson, D; Connolly, J
Abstract : Background: Trauma strikes unexpectedly, frequently in the young and fit. When trauma victims arrive in the emergency room all possible steps, including surgery, are often undertaken in an attempt to achieve a successful outcome. However, for patients presenting in extremis, with cardiac arrest or exsanguinating blunt chest injury, the results of resuscitation and emergency surgery are extremely poor. Patients and setting: Eight patients in extremis with a mean injury severity score of 36, presented to the resuscitation room of Queens Medical Centre during 2001. On arrival all were in extremis or cardiac arrest after significant blunt injury to the torso, and during resuscitation had a brief loss of cardiac output. They underwent emergency surgery to control haemorrhage and correct injuries in an attempt to preserve life. Seven patients died within hours of their initial presentation either in theatre or the intensive care unit and one patient survived. Conclusions: Futile care in the management of severely injured patients is a controversial concept although the literature defines four concepts of futility within surgery. At present, while there remains even the remotest possibility of survival, there remains a strong incentive to act and reports of isolated survivors from studies of trauma patients in extremis or cardiac arrest continue to emerge. This may be seen as justification for either an aggressive surgical approach or an indication that surgery is futile. In an emerging culture of guidelines regarding effectiveness of treatment, is this an area in which such guidelines can or should be applied?